The impact of biodiversity information on willingness to pay - Hörisch, Jacob; Petersen, Lars; Jacobs, Kathleen (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2025)
Biodiversity loss is one of the planetary boundaries that is most urgently in need of action. However, very little is known about the consumers’ willingness to pay (WTP) for products with higher (or lower) levels of biodiversity performance. Therefore, this research was conducted to investigate how consumers’ WTP is influenced by a product's impact on biodiversity. To address this question, we collected representative data from 524 German consumers in a survey-based experiment. Drawing on prospect theory, we identified the shape of the WTP reaction function for a given product in relation to its biodiversity performance. We demonstrate that consumers with sufficiently high levels of education and concern about biodiversity loss are willing to pay more for products with above-average biodiversity performance and less for products with below-average biodiversity performance. However, the extent to which a product outperforms the industry average does not influence consumers’ increased WTP. From a sustainable development perspective, these observed patterns highlight the problematic contrast between the pressing need for substantial improvements in product biodiversity performance and the limited incentives provided by consumers. Consequently, the findings suggest that the incentives that consumers currently provide for corporate biodiversity management are insufficient to assist in staying within the planetary boundaries.
Keywords: Biodiversity Footprint; Consumer Behavior; Industrial Ecology; Prospect Theory; Sustainable Consumption; Willingness To Pay (WTP)